Renewable Polymers: Processing and Chemical Modifications - Mekonnen, Tizazu (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The utilization of bio-resourced macromolecules for polymer applications has been the subject of increasing interest, mainly for sustainability and functionality reasons. This Special Issue of Processes brings together nine papers from leading scientists and researchers active in the area of "Sustainable and Renewable Polymers, Processing, and Chemical Modifications". The collected papers include seven original research and two review articles related to renewable feedstock for polymer applications, processes for the fabrication of renewable polymer-based nanomaterials, the design and modification of renewable polymers, and applications of renewable polymers. The journal Processes will continue to nurture progress in this field through its position as an open access platform.